Turkish /h/ deletion: evidence for the interplay of speech perception and phonology - Mielke, Jeff (ZAS Papers in Linguistics, 2002)
It has been hypothesized that sounds which are less perceptible are more likely to be altered than more salient sounds, the rationale being that the loss of information resulting from a change in a sound which is difficult to perceive is not as great as the loss resulting from a change in a more salient sound. Kohler (1990) suggested that the tendency to reduce articulatory movements is countered by perceptual and social constraints, finding that fricatives are relatively resistant to reduction in colloquial German. Kohler hypothesized that this is due to the perceptual salience of fricatives, a hypothesis which was supported by the results of a perception experiment by Hura, Lindblom, and Diehl (1992). These studies showed that the relative salience of speech sounds is relevant to explaining phonological behavior. An additional factor is the impact of different acoustic environments on the perceptibility of speech sounds. Steriade (1997) found that voicing contrasts are more common in positions where more cues to voicing are available. The P-map, proposed by Steriade (2001a, b), allows the representation of varying salience of segments in different contexts. Many researchers have posited a relationship between speech perception and phonology. The purpose of this paper is to provide experimental evidence for this relationship, drawing on the case of Turkish /h/ deletion.